Pendampingan Sosialisasi Bullying Siswa Kelas 4, 5, dan 6 SDN 1 Pekon Balak - Devi, Yulistia; Rossi, Angelita; Arsanti, Dwi; Cantika, Fadiya Puteri; Sari, Putri Ratna (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service activity aims to convey information about community service programs that focus on preventing bullying among students at SDN 1 Pekon Balak. This socialization is designed as an educational effort to prevent students from becoming victims or perpetrators of bullying. The methods used in this activity include delivering material through lectures or socialization sessions. The output of this activity is an increase in students' understanding of the types of bullying, its causes, its impacts, and how to reduce bullying behavior. This activity also succeeded in encouraging students to develop self-control and practice positive habits in the family, school, and community environments.